EService-Learning: A Decade of Research in Undergraduate Online Service–learning. Issue 2 (3rd April 2021) - Faulconer, Emily
ABSTRACT: With an increasing number of courses taught asynchronously online, it is important to explore how to implement high-impact practices in this modality. Service-learning – a high impact practice – is a course-based, credit-bearing type of experiential learning. It is important to understand instructional strategies and course design for service-learning in the online modality. This review provides an analysis of the last decade of research of Type II and Type IV eService-Learning (with service component online). Analysis of the literature reveals the absence of STEM disciplines, cursory attention to detailing reflection and assessment in describing learning environments in eService-Learning research, and heavy reliance on self-reported, subjective measures. This study presents a framework for performing service-learning fully online, regardless of discipline. Finally, this paper presents a clear call to research – one that aims at resolving unknowns within eService-Learning.